2012
DOI: 10.1016/j.expneurol.2011.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Blood serum miRNA: Non-invasive biomarkers for Alzheimer's disease

Abstract: There is an urgent need to identify non-invasive biomarkers for the detection of sporadic Alzheimer’s disease (AD). We previously studied microRNAs (miRNAs) in AD autopsy brain samples and reported a connection between miR-137, -181c, -9, -29a/b and AD, through the regulation of ceramides. In this study, the potential role of these miRNAs as diagnostic markers for AD was investigated. We identified that these miRNAs were down-regulated in the blood serum of probable AD patients. The levels of these miRNAs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
184
4
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(195 citation statements)
references
References 55 publications
6
184
4
1
Order By: Relevance
“…Dong et al (2015) found that the expression of miR-93-5p in AD patients was 0.48 times that in control subjects, a finding consistent with those of the current study. Some studies have also reported the lower levels of miR-137, 181c, 9, 29a, and 29b in the serum of patients with mild cognitive impairment (Geekiyanage et al 2012). Although the expression levels of some of these miRNAs changed in the current study, the copy numbers were below 400; therefore, those miRNAs cannot be used as biomarkers.…”
Section: Discussioncontrasting
confidence: 61%
“…Dong et al (2015) found that the expression of miR-93-5p in AD patients was 0.48 times that in control subjects, a finding consistent with those of the current study. Some studies have also reported the lower levels of miR-137, 181c, 9, 29a, and 29b in the serum of patients with mild cognitive impairment (Geekiyanage et al 2012). Although the expression levels of some of these miRNAs changed in the current study, the copy numbers were below 400; therefore, those miRNAs cannot be used as biomarkers.…”
Section: Discussioncontrasting
confidence: 61%
“…The levels of these miRNAs were also reduced in the serum of AD risk factor models. Although the ability of these miRNAs to conclusively diagnose AD is currently unknown, it was suggested as a potential use for circulating miRNAs, along with other markers, as non-invasive and relatively inexpensive biomarkers for the early diagnosis of AD (62). However, circulating mRNAs could be useful in a complex neuropsychiatric disorder that involves disturbances in neural circuitry and synaptic function as in schizophrenia.…”
Section: Circulating Mirnas In Autoimmune Diseases Inflammatory and mentioning
confidence: 99%
“…The role for miR-137 in SZ pathogenesis was further corroborated by the validation of SZ-associated genes CSMD1, C10orf26, CACNA1C, and TCF4 as miR-137 targets [67]. Nevertheless, it is perhaps not surprising that miR-137 has not emerged as a (specific) SZ biomarker: similar to miR-134 and miR-15-107 family, miR-137 was found to be dysregulated in other diseases [68,69].…”
Section: Discussionmentioning
confidence: 91%